Cytogenetical characterization of Acalypha indica L. in Bangladesh - Bonna, Ishrat Jahan; Alam, Sheikh Shamimul; Sultana, Syeda Sharmeen (Dhaka University Journal of Biological Sciences, 2018)
Acalypha indica L. was cytogenetically characterized after staining with orcein, CMA and DAPI. In this species "Simple Chromocenter Type" of interphase nuclei was observed with a few small heterochromatin blocks following orcein staining. Prophase chromosomes showed “Interstitial Type” of staining pattern with orcein which indicated the tendency of aggregation of heterochromatin in interstitial regions of chromosome. This plant was found to possess 2n = 20 metacentric chromosomes. The total length of 2n chromosome complement was 55.33 μm. Individual chromosome length ranged from 1.84 to 3.50 μm. The relative length of each chromosome ranged from 0.03 to 0.06. After staining with CMA, three bright bands were observed at different locations of chromosomes. A total of four DAPI-positive bands were also found of which two bands were centromeric and other two were entirely fluoresced with DAPI. The results of the cytological investigation may be useful for future characterization of this plant species. Dhaka Univ. J. Biol. Sci. 27(2): 183-189, 2018 (July)